Health care service utilization among elderly in rural setting of Gandaki province, Nepal: a mixed method study - Poudel, Kamal; Malla, Dinesh Kumar; Thapa, Kanchan (Frontiers in Health Services, 2024)
IntroductionGlobally, one in every six people will be elderly by 2030. In Nepal, there has been a notable rise in the aging and elderly. Addressing the healthcare needs of them is crucial. Despite the different efforts to advocate for healthy aging, various factors continue to limit this process. This paper aims to explore the utilization of healthcare services among the elderly population and uncover influences on the ability to access these services.MethodA mixed-method community-based study was conducted in Bihadi Rural Municipality of Parbat, Nepal. The quantitative segment involved interviews with 355 individuals aged ≥60 years, while 18 respondents were enlisted for in-depth interviews. We used descriptive statistics, chi-square test, and logistic regression in quantitative analysis. Similarly, content and thematic analysis were performed in the qualitative component.ResultsThis study reported that health service utilization among the respondents was 65.4%. Among the factors ethnicity (OR 3.728, 95% CI 1.062–15.887), not good health status (OR 2.943, 95% CI 1.15–8.046), bus as means of transportation (OR 8.397, 95% CI 1.587–55.091) had higher odds whereas government hospital (OR 0.046, 95% CI 0.009–0.193), not always available health staffs (OR 0.375, 95% CI 0.147–0.931), not sufficient medicine (OR 0.372, 95% CI 0.143–0.924), not available medicine (OR 0.014, 95% CI 0.002–0.068) had lower odds for health service utilization. Other factors identified from qualitative components include long waiting times, insufficient medicine, lack of trained health personnel, financial capacity, low utilization of health insurance, distance, and support from family members.ConclusionsNonetheless, a portion of the elderly remained excluded from mainstream of healthcare services. A combination of social, healthcare-related, and individual factors influences the utilization of healthcare services. To ensure elderly-friendly services, prioritize geriatric care training, secure medication availability, and establish a dedicated health insurance program for them. In the current federal context, localizing evidence-based, innovative strategies to address the healthcare needs of the elderly is crucial.